Reality check : how science deniers threaten our future - Prothero, Donald R. (Bloomington and Indianapolis : Indiana University Press, 2013)
The battles over evolution, climate change, childhood vaccinations, and the causes of AIDS, alternative medicine, oil shortages, population growth, and the place of science in our country, all are reaching a fevered pitch. Many people and institutions have exerted enormous efforts to misrepresent or flatly deny demonstrable scientific reality to protect their nonscientific ideology, their power, or their bottom line. To shed light on this darkness, the author explains the scientific process and why society has come to rely on science not only to provide a better life but also to reach verifiable truths no other method can obtain. He describes how major scientific ideas that are accepted by the entire scientific community (evolution, anthropogenic global warming, vaccination, the HIV cause of AIDS, and others) have been attacked with totally unscientific arguments and methods. He argues that science deniers pose a serious threat to society, as their attempts to subvert the truth have resulted in widespread scientific ignorance, increased risk of global catastrophes, and deaths due to the spread of diseases that could have been prevented.
Reality check -- Science, our candle in the darkness -- Betrayers of the truth: selling out science -- Making the environment the enemy: acid rain, the ozone hole, and the demonization of Rachel Carson -- Hot enough for you? The heated debate over a warming planet -- Gimme that old time religion: creationism, intelligent design, and the denial of humanity's place in nature -- Jenny's body count: playing Russian roulette with our children -- Victims of modern witch doctors: AIDS denialism -- If it quacks like a quack: snake-oil con artists in an era of medical science -- What's your sign? the ancient pseudoscience of astrology -- Down the slope of Hubbert's curve: the end of cheap oil and natural resources -- Far from the madding crowd: human overpopulation and its consequences -- The rejection of reality: how the denial of science threatens us all.
Includes bibliographical references and index.
Keywords: Pseudoscience; Science -- Social aspects; Science -- Political aspects; Pseudoscience; Science -- Political aspects; Science -- Social aspects; Pseudowissenschaft; Gesellschaft